Sexual and reproductive health service utilization and associated factors among youth workers at Kombolcha Industry Park, Kombolcha town, Northeast Ethiopia, 2023 - Endalew, Addisu; Kefale, Bereket; Atnafu Gebeyehu, Natnael; Birhan, Belete (Frontiers in Public Health, 2024)
Background Youth is a decisive age that shapes the direction of their life and that of their family. However, due to the host of biological, social, and economic factors, youth Industry Park workers can be at high risk of adverse sexual and reproductive health outcomes. Therefore, assessing youth sexual and reproductive health service utilization and associated factors among youth workers is very crucial for timely intervention to their gaps. Objective This study aimed to assess sexual and reproductive health service utilization and associated factors among youth workers working at Kombolcha Industry Park Kombolcha, Northeast Ethiopia, 2023. Methods An institutional-based cross-sectional study was conducted at Kombolcha Industry Park, Kombolcha, among a total of 422 youth workers from 1 January to 30 January 2023. A simple random sampling technique was used to access a total of 422 youth workers in Kombolcha Industry Park. The data were collected using pre-test, structured, and interviewer-administered questionnaires. Data were entered into Epi Data version 3.1 and were exported to SPSS version 26 for analysis. Bi-variable and multivariable binary logistic regression analyses were performed. Adjusted odds ratio with 95% confidence interval was estimated to measure the strength of the association. The level of statistical significance was declared at a p value of less than 0.05. Results Overall utilization of reproductive health services was 45.50%. Being married [adjusted odds ratio (AOR) = 5.76, 95% CI (2.94, 11.25)], near distance of sexual and reproductive health (SRH) facility to home [AOR = 2.57, 95% CI (1.60, 4.14)], having good knowledge [AOR = 9.23 95%CI (4.88, 17.44)], and good attitude about SRH [AOR = 2.06 95% CI (1.29, 3.28)] were significantly associated with youth SRHs utilization. Conclusion Youth sexual and reproductive health service utilization among youth workers of Kombolcha Industry Park was low. Ensuring SRHs availability and accessibility, empowering youth with knowledge of SRHs, and advocating sexual and reproductive health services to develop a good attitude might be important in improving reproductive health service utilization. Future researchers should address segments of the population other than Kombolcha Industry Park.